A compact TM03 mode penta‐polarization agile MSA for interference mitigation in 5G ultra‐dense point to point environment. Issue 10 (22nd June 2022) - Pal, Joydeep; Patra, Kaushik; Gupta, Bhaskar
Abstract: Signal interference in the recent 5G ultra‐dense environment is becoming severe due to the co‐existence of large RF nodes operating in the constrained spectrum. In this article, a polarization agile approach for the designing of an RF system is studied to mitigate interference issues besides the communication and signal processing approach. A compact single‐fed single layer penta‐polarization agile higher‐order microstrip patch is analyzed probably for the first time in the literature. The proposed antenna possesses a very low profile of less than 0.01 λ (λ free‐space wavelength). Reconfigurable orthogonal feeding with switches is connected with the horizontal and vertical patch edges. Subsequently, these are excited separately and simultaneously using switchable PIN diodes and appropriate bias networks to realize horizontal, vertical, and 45° slant polarization states. Successively, diagonal patch corners are truncated to initiate right and left‐hand circular polarizations. Slots are etched on specific orientation of currents on the patch surface to improve side‐lobe levels. A prototype is analyzed, simulated, and fabricated at TM03 mode and operating at 5.8 GHz band with penta‐polarization agility. A consistent 11 dBi realized broadside gain is measured covering the 10 dB reflection loss and 3 dB axial ratio bandwidth in both the principal planes.